Catheter‐associated deep vein thrombosis in children with severe traumatic brain injury: A single‐center experience. Issue 1 (17th October 2022) - Lovett, Marlina E.; Daniel, Megan; Keesari, Rohali; MacDonald, Jennifer; Rodriguez, Vilmarie; Muszynski, Jennifer; Sribnick, Eric A.; O'Brien, Nicole F.; Ayad, Onsy
Abstract: Background: This study was performed to describe the single‐center experience of deep vein thrombosis (DVT) in children with severe traumatic brain injury (sTBI) who were mechanically ventilated with a central line, and to identify potentially modifiable risk factors. It was hypothesized that children with DVT would have a longer duration of central venous line (CVL) and a higher use of hypertonic saline (HTS) compared to those without DVT. Procedure/methods: This was a retrospective study of children (0–18 years) with sTBI, who were intubated, had a CVL, and a minimum intensive care unit (ICU) stay of 3 days. Children were analyzed by the presence or absence of DVT. HTS use was evaluated using milliliter per kilogram (ml/kg) of 3% equivalents. Univariable and multivariable logistic regression models were used to determine which factors were associated with DVT. Results: Seventy‐seven children met inclusion criteria, 23 (29.9%) had a DVT detected in an extremity. On univariable analysis, children with DVT identified in an extremity had prolonged CVL use (14 vs. 8.5 days, p = .021) and longer duration of mechanical ventilation (15 vs. 10 days, p = .013). HTS 3% equivalent ml/kg was not different between groups. On multivariable analysis, mechanical ventilation duration was associated with DVT detection in an extremity, whereas neither CVL duration nor HTS use had an association. Conclusions: There was a high incidence of extremity DVT detected in children with sTBI who received invasive mechanical ventilation and had a CVL. HTS administration was not associated with DVT detection in an extremity.